Reduction of radiocaesium transfer to broiler chicken meat by the hexacyanoferrate-cellulose binder "Bifezh" - Pöschl, Michael; Rezác, Petr (Radiation and environmental biophysics, 2004)
The influence of Bifezh (a hexacyanoferrate compound as veterinary feed additive) on the transfer of (137)Cs to meat was investigated in broiler chickens after application of an artificially contaminated feed mixture. The reduction factors reached 2.23 and 8.46 for single and multiple (137)Cs administration, respectively. The elimination rate of (137)Cs in the decontamination period was only slightly increased by Bifezh. The reduction effect of Bifezh was considerably and positively limited by various amounts of the additive during both radiocaesium accumulation and decontamination. No significant differences in the reduction effect between breast and thigh meat were observed. In conclusion, the hexacyanoferrate-cellulose binder Bifezh can be recommended as an alternative chemical measure for reducing (137)Cs contamination of broiler chicken meat, although administration rates may need to be enhanced over those currently recommended.
Keywords: Breast; Food Contamination, Radioactive; Radiation Protection; Radiation-Protective Agents; radioizotopy cesia; prsy; metabolická clearance; krmivo pro zvířata; maso; ferrokyanidy; aplikace orální; Muscle, Skeletal; drůbeží výrobky; Poultry Products; Ferrocyanides; radioaktivní kontaminace potravin; stehno; Cesium Radioisotopes; kosterní svaly; Thigh; Meat; Administration, Oral; Animal Feed; radiační ochrana; Metabolic Clearance Rate; radioprotektivní látky